The Pathogenesis and Immune Evasive Mechanisms of Equine Herpesvirus Type 1 - Laval, Kathlyn; Poelaert, Katrien C. K.; Van Cleemput, Jolien; Zhao, Jing; Vandekerckhove, Annelies P.; Gryspeerdt, Annick C.; Garré, Barbara; van der Meulen, Karen; Baghi, Hossein B.; Dubale, Haileleul N.; Zarak, Ines; Van Crombrugge, Eline; et al. (Frontiers in Microbiology, 2021)
Equine Herpesvirus type 1 (EHV1) is an alphaherpesvirus related to pseudorabies virus (PRV) and varicella-zoster virus (VZV). This virus is one of the major pathogens affecting horses worldwide. EHV1 is responsible for respiratory disorders, abortion, neonatal foal death and equine myeloencephalopathy (EHM). Over the last decade, EHV1 has received growing attention due to the frequent outbreaks of abortions and/or EHM causing serious economical losses to the horse industry worldwide. To date, there are no effective antiviral drugs and current vaccines do not provide full protection against EHV1-associated diseases. Therefore, there is an urgent need to gain a better understanding of the pathogenesis of EHV1 in order to develop effective therapies. The main objective of this review is to provide state-of-the-art information on the pathogenesis of EHV1. We also highlight recent findings on EHV1 immune evasive strategies at the level of the upper respiratory tract, blood circulation and endothelium of target organs allowing the virus to disseminate undetected in the host. Finally, we discuss novel approaches for drug development based on our current knowledge of the pathogenesis of EHV1.